1991
DOI: 10.1128/jb.173.9.2776-2785.1991
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, sequencing, and expression of a gene encoding a 100-kilodalton mosquitocidal toxin from Bacillus sphaericus SSII-1

Abstract: A cosmid library was prepared from a partial BamHJ digest of total DNA from Bacillus sphaericus SSII-1. Two hundred fifty Escherichia coli clones were screened for toxicity against larvae of the mosquito Culex quinquefasciatus. One toxic clone, designated pKF2, was chosen for further study. Two toxic subclones, designated pXP33 and pXP34, obtained by ligating PstI-derived fragments of pKF2 into pUC18, contained the same 3.8-kb fragment, but in opposite orientations. Sequence analysis revealed the presence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
102
0
2

Year Published

1993
1993
2006
2006

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(107 citation statements)
references
References 37 publications
3
102
0
2
Order By: Relevance
“…The binary action of the 42 and 51 kDa peptides in the process of toxicity of B. sphaericus has been established (Broadwell et al 1990, Davidson et al 1990). The role of a third 100 KDa toxin previously characterized (Davidson 1983) which may be influencing the results obtained in this research has been established elsewhere (Thanabalu et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The binary action of the 42 and 51 kDa peptides in the process of toxicity of B. sphaericus has been established (Broadwell et al 1990, Davidson et al 1990). The role of a third 100 KDa toxin previously characterized (Davidson 1983) which may be influencing the results obtained in this research has been established elsewhere (Thanabalu et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…4. Comparison of the amino acid sequences of the region adjacent to a glutamic acid residue suggested to be involved in catalysis of the ADP-ribosylation by various transferases (Lim, C. limosum ADP-ribosyltransferase [28]; C3N, C. botulinum C3 transferase [26]; C3P, C. botulinum C3 transferase [25]; EDIN, S. aureus transferase [27]; Cer, B. cereus transferase [23]; CT, cholera toxin [30]; LT, E. coli heat labile toxin [43]; MTX, mosquitocidal toxin from B. sphaericus [44]; PT, pertussis toxin [45]; T2, bacteriophage ADPribosyltransferase T2 [32]; mRT6, mouse homologue of the rat T cell alloantigen RT6 [46]; rMT, rabbit muscle ADP-ribosyltransferase [33]; ETA, Pseudomonas exotoxin A [47]; DT, diphtheria toxin [481.…”
Section: Resultsmentioning
confidence: 99%
“…The N-terminal region of the Mtx protein was found to have significant regional homology to the catalytic subunits of ADP-ribosyltransferase (32) toxins, such as the pertussis toxin S1 subunit (26), and had no significant homology with the 51.4-and 41.9-kDa toxins from the high-toxicity B. sphaericus strains (32). In earlier studies (31), a 97-kDa protein, Mtx21 (amino acids 30 to 870), derived from the 100-kDa mosquitocidal protein (Mtx) of B. sphaericus SSII-1 by the deletion of the putative signal sequence, was expressed as a fusion protein with glutathione S-transferase (GST) in Escherichia coli and purified by affinity chromatography.…”
mentioning
confidence: 99%
“…Early studies indicated that the toxin was very unstable, was produced predominantly before the onset of sporulation, and was associated with the cell pellet (23, 24). The genes encoding the 51.4-and 41.9-kDa binary toxin have been shown to be absent from B. sphaericus SSII-1 (4).To study the nature of the toxicity of B. sphaericus SSII-1, we have cloned a gene encoding a 100-kDa protein and have designated it the mix (mosquitocidal-toxin) gene (32). The N-terminal region of the Mtx protein was found to have significant regional homology to the catalytic subunits of ADP-ribosyltransferase (32) toxins, such as the pertussis toxin S1 subunit (26), and had no significant homology with the 51.4-and 41.9-kDa toxins from the high-toxicity B. sphaericus strains (32).…”
mentioning
confidence: 99%
See 1 more Smart Citation